DENTAL ANTIBIOTIC PROPHYLAXIS IN TOTAL JOINT REPLACEMENT: AN UPDATED REVIEW OF GUIDELINES AND CLINICAL STUDIES - Dan Mihailescu; Norin Forna; Paul Dan Sirbu; Tudor Pinteala; Mihnea Theodor Sirbu; Dana Nicoleta Mihai; Liliana Savin (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study: This review evaluates the necessity and effectiveness of antibiotic prophylaxis in preventing prosthetic joint infections (PJI) following dental procedures in patients with joint implants.Material and methods: An extensive literature review was conducted, focusing on studies evaluating the link between dental care and PJI. Sources included PubMed and other databases, using terms such as dental care, joint prosthesis, and antibiotic prophylaxis. The review spanned papers from 2003 to 2023, with a focus on hip and knee joint replacements and dental procedure-related prophylaxis guidelines.Results: The review found that the prevalence of dental pathology in patients with total hip arthroplasty (THA) or total knee arthroplasty (TKA) varied significantly. Studies indicated no significant benefit of antibiotic prophylaxis in reducing PJI risk post-dental procedures. Furthermore, the incidence of PJI was not significantly different in patients receiving antibiotic prophylaxis compared to those who did not. It was observed that routine activities, such as chewing and brushing, contribute more to bacteremia and potential joint infection than dental procedures themselves.Conclusions: The evidence suggests that antibiotic prophylaxis for dental procedures in patients with joint prostheses is not universally beneficial and should not be routinely recommended. Emphasis on individual risk assessment, maintenance of good oral hygiene, and adherence to evidence-based guidelines is paramount. The study advocates for personalized approaches to PJI prevention, aligning with the goals of antibiotic stewardship and patient safety.